The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep27209
|View full text |Cite
|
Sign up to set email alerts
|

miR-21-5p renal expression is associated with fibrosis and renal survival in patients with IgA nephropathy

Abstract: IgA nephropathy (IgAN) is the most prevalent primary glomerulonephritis, whose prognosis is highly variable. Interstitial fibrosis is a strong independent prognosis factor. Among microRNA involved in renal fibrogenesis, only few have been investigated in IgAN. In the context of IgAN, we aimed to analyze the role of miR-21-5p, miR-214-3p and miR-199a-5p, three established “fibromiRs” involved in renal fibrosis. Fifty-six IgAN biopsy specimens were retrospectively scored according to Oxford classification. Renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 42 publications
10
56
0
Order By: Relevance
“…After measuring renal expression of miR-21-5p, miR-214-3p, and miR-199a-5p levels, Hennino et al confirmed that miR-21-5p acted as a “fibromiRs”, participated in the course of IgAN and closely linked with renal survival [25]. Furthermore, several publications suggested that circulating miRNAs levels might also represent a novel, predictive and reliable blood marker of kidney fibrosis [32-34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After measuring renal expression of miR-21-5p, miR-214-3p, and miR-199a-5p levels, Hennino et al confirmed that miR-21-5p acted as a “fibromiRs”, participated in the course of IgAN and closely linked with renal survival [25]. Furthermore, several publications suggested that circulating miRNAs levels might also represent a novel, predictive and reliable blood marker of kidney fibrosis [32-34].…”
Section: Discussionmentioning
confidence: 99%
“…Allow for previous reports of heightened renal MMP-7 expression in renal fibrosis and the significance of kidney fibrosis implicated in the pathogenesis of IgAN [25, 26], we hypothesized that the intrarenal fibrosis signature could be detected noninvasively by quantification of MMP-7 level in circulation and, it might serve as a noninvasive prognostic biomarker in IgAN. Since MMP-7 expression is little investigated in IgAN by now, in this study, we examined the association of serum MMP-7 level and histopathological change, as well as the renal progression of IgAN in a cohort of biopsy proven patients.…”
Section: Introductionmentioning
confidence: 99%
“…This model has proven to be useful in identifying key stress-induced microRNAs, such as miR-21 and miR-214 (Denby et al, 2011), which are upregulated during renal injury. These microRNAs have since been found to be differentially expressed in human biopsies of individuals with IgA nephropathy, and their upregulation correlates linearly with renal fibrosis (Hennino et al, 2016), demonstrating the translational relevance of this model.…”
Section: Models Of Acute and Chronic Kidney Diseasementioning
confidence: 96%
“…Later, our lab was able to effectively differentiate AKI patients from healthy patients by measuring miR-21 combined with miR-200c, miR-423 and miR-4640 in urine[114]. Since then, miR-21 has been found to be a reliable biomarker of drug-induced kidney injury[110] and fibrosis[115], and was associated with kidney injury from multiple chronic diseases including type 2 diabetes and IgA nephropathy[116, 117]. …”
Section: Mirnas In Kidney Injury and Repairmentioning
confidence: 99%